2006
DOI: 10.4141/p06-105
|View full text |Cite
|
Sign up to set email alerts
|

Response of cucumber to timing of fertilizer application in southwest Nigeria

Abstract: . 2006. Response of cucumber to timing of fertilizer application in southwest Nigeria. Can. J. Plant Sci. 86: 1391-1394. A field trial was conducted at the experimental farm of the Department of Crop Protection and Environmental Biology, University of Ibadan, Nigeria, to determine the growth and yield response of cucumber (cv. Poinsett) to timing of fertilizer application. Fertilizer (20:10:10), at the rate of 150 kg N ha -1 , was applied at: planting, 3 weeks after planting (WAP) and 6 WAP. Similarly, split a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(6 reference statements)
2
1
0
Order By: Relevance
“…Ingram et al (1998) observed that some tree seedlings do not generally respond to nitrogen fertilizers in excess of about 24 g m -2 . The present results agree with the observation of Odeleye et al (2006) that urea increased number of leaves among other growth traits. Nitrogen is the only nutrient supplied by urea, whose increase in rate tended to reduce the number of leaves of P. erinaceous in this study.…”
Section: Number Of Leavessupporting
confidence: 93%
See 1 more Smart Citation
“…Ingram et al (1998) observed that some tree seedlings do not generally respond to nitrogen fertilizers in excess of about 24 g m -2 . The present results agree with the observation of Odeleye et al (2006) that urea increased number of leaves among other growth traits. Nitrogen is the only nutrient supplied by urea, whose increase in rate tended to reduce the number of leaves of P. erinaceous in this study.…”
Section: Number Of Leavessupporting
confidence: 93%
“…The above result is in consonance with the work of Odeleye et al (2006) who observed that early application of inorganic fertilizers tends to increase vegetative growth of plant particularly the leaf area, since it is at this stage that plant will concentrate more assimilate to vegetative structures and improve nutrition of sites which tend to enhance stem elongation and leaf area development. This agrees with the submission of Agbede et al (2018) and Aderounmu ans Olajuyigbe(2019).…”
Section: Seedlings Leaf Areasupporting
confidence: 89%
“…NPK (20:10:10) fertilizer were applied at the rate of 30kg/ha. At land preparation 16 kg/ha fertilizer were applied at 3weeks after sowing (WAS) and the remaining at 6 WAS (Odeleye and Adedokun, 2006), plants were thinned to two per stand two weeks after emergence.…”
Section: Methodsmentioning
confidence: 99%
“…It is however important to note that fertiliser application should be based on soil test results. Fertiliser should be best applied at 3-6 WAP [36].…”
Section: Low Soil Fertilitymentioning
confidence: 99%